PENGARUH KONEKSI POLITIK, KEPEMILIKAN INSTITUSIONAL DAN KOMISARIS INDEPENDEN TERHADAP AGRESIVITAS PAJAK - Sintia Dewi Kartikasari; Eka Oktapiani (Jurnal Nusa Akuntansi, 2026)
This study aims to determine the effect of political connections, institutional ownership, and independent commissioners on tax aggressiveness. This type of research is quantitative research. The population in this study were energy companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The sample of this study used purposive sampling technique by meeting certain criteria in accordance with the research objectives. The number of companies that became research samples was 14 companies. Data processing using Eviews 13 with the help of Microsoft Excel by analyzing descriptive statistics, model selection test, classical assumption test, coefficient of determination, panel data regression analysis, F statistical test and t statistical test. The results showed that simultaneously political connections, institutional ownership, and independent commissioners had an effect on tax aggressiveness. Partially independent commissioners have an effect on tax aggressiveness. Meanwhile, political connections and institutional ownership have no effect on tax aggressiveness.